ANALISIS INTERFERENSI WIRELESS LAN IEEE 802.11n TERHADAP BLUETOOTH PADA FREKUENSI 2,4GHz DENGAN VARIASI JARAK - Danial Risaf Ashari; Sigit Kusmaryanto; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2017)
Abstract – This research is discuss about analysis interferance WLAN 802.11n toward bluetooth in frequency 2,4 GHz with distance variation between laptop user and changing bluetooth. Using the same frequency band makes WLAN 802.11n and bluetooth can interferance each other. This research tested in an open space which certainly there is no one using 2.4 GHz frequency except researcher. The Spectrum Analyzer tool is used to determine the condition of use of the 2,4 GHz in the test area. This research is conducted by counting 3 parameters Quality of Service (QoS) that are delay, throughput, and packet loss. The result indicate that there is an effect of 802.11n WLAN performance if interference toward bluetooth. The value of delay, throughput, and packet loss has change when interference by bluetooth if compared with WLAN 802.11n network without interference. The value of delay, throughput, and packet loss without interference are 4,8115 ms, 1820 Kbit/s, 0%. Whereas, the value of delay in 1m, 2m, 3m, 4m, and 5m distance are 7,7526 ms, 7,2608 ms, 6,5611 ms, 6,3994 ms, 5,5657 ms. The value of troughput in 1m, 2m, 3m, 4m, and 5m distance are 1052,333 Kbit/s, 1149,333 Kbit/s, 1330,333 Kbit/s, 1370 Kbit/s, 1800 Kbit/s. The value of packet loss in WLAN 802.11n network for all interference distances is still very good  (0% ≤ PL <3%) based on TIPHON (Telecommunications and Internet Protocol Harmonization Over Networks) standard. Key word: WLAN 802.11n, bluetooth, Quality of Service (QoS), TIPHON Abstrak — Penelitian ini membahas tentang analisis interferensi WLAN 802.11n terhadap bluetooth pada frekuensi 2,4 GHz dengan variasi jarak antara laptop user dengan bluetooth yang berubah ubah. Penggunaan pita frekuensi yang sama membuat WLAN 802.11n dan bluetooth dapat saling interferensi. Pengujian penelitian ini dilakukan pada ruang terbuka yang dipastikan tidak ada penggunaan frekuensi 2,4 GHz lainnya selain penguji. Alat Spectrum Analyzer digunakan untuk mengetahui kondisi penggunaan frekuensi 2,4 GHz di daerah pengujian. Penelitian ini dilakukan dengan menghitung 3 parameter Quality of Service (QoS) yaitu delay, throughput, dan pakcet loss. Hasil pengujian menunjukkan bahwa adanya pengaruh kinerja WLAN 802.11n jika terinterferensi terhadap bluetooth. Nilai delay, throughput, dan pakcet loss mengalami perubahan saat terinterferensi oleh bluetooth jika dibandingkan dengan jaringan WLAN 802.11n  tanpa interferensi. Nilai delay, throughput, dan pakcet loss tanpa interferensi adalah sebesar 4,8115 ms, 1820 Kbit/s, 0 %. Sedangkan besar nilai delay pada jarak 1m, 2m, 3m, 4m, dan 5m adalah sebesar 7,7526 ms, 7,2608 ms, 6,5611 ms, 6,3994 ms, 5,5657 ms. Nilai throughput pada jarak 1m, 2m, 3m, 4m, dan 5m adalah sebesar 1052,333 Kbit/s, 1149,333 Kbit/s, 1330,333 Kbit/s, 1370 Kbit/s, 1800 Kbit/s. Nilai packet loss pada jaringan WLAN 802.11n yang terinterferensi untuk semua jarak interferensi masih termasuk kategori sangat bagus (0% ≤ PL < 3%) berdasarkan standart TIPHON (Telecommunications and Internet Protocol Harmonization Over Networks). Kata Kunci – WLAN 802.11n, bluetooth, Quality of Service (QoS), TIPHON.